La stérilité d'origine immunologique. - De Muylder, X (1984)
Antispermatozoal antibodies in the woman, the man, or both, may be the cause of nonorganic infertility in a small number of couples. The antibodies are most often found in the serum or in the genital fluids. Diagnosis is based on the postcoital test and on various laboratory tests to assess sperm-cervical mucous compatibility and to detect antispermatozoal antibodies. In women the strongest relation between results of laboratory tests and infertility is between the presence of serum antispermatozoal antibodies and infertility of more than 3 years' duration. In men there is a relation between high levels of these antibodies in the semen and infertility. Various treatments have been proposed, but further prospective studies are needed. However, promising results have been reported with homologous intrauterine insemination and with immunosuppression in men.